2017
DOI: 10.3389/fmicb.2016.02064
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbiome Is More Heterogeneous in Organic Than in Conventional Farming System

Abstract: Organic farming system and sustainable management of soil pathogens aim at reducing the use of agricultural chemicals in order to improve ecosystem health. Despite the essential role of microbial communities in agro-ecosystems, we still have limited understanding of the complex response of microbial diversity and composition to organic and conventional farming systems and to alternative methods for controlling plant pathogens. In this study we assessed the microbial community structure, diversity and richness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
169
5
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(200 citation statements)
references
References 70 publications
17
169
5
9
Order By: Relevance
“…inputs and tillage have been shown to shape bulk soil microbial communities and functions across spatial and temporal scales (1)(2)(3)(4). Comparisons of bulk soil under different management strategies, i.e., organic (nutrients provided from sources other than synthetic inputs) versus conventional management, have revealed effects on soil properties that, in turn, drive variation in microbial communities at small and intermediate scales (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…inputs and tillage have been shown to shape bulk soil microbial communities and functions across spatial and temporal scales (1)(2)(3)(4). Comparisons of bulk soil under different management strategies, i.e., organic (nutrients provided from sources other than synthetic inputs) versus conventional management, have revealed effects on soil properties that, in turn, drive variation in microbial communities at small and intermediate scales (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In the past, researchers have reported increased soil bacterial biomass, activity and bacterial functional and taxonomic richness and diversity in organic farm (Gardner et al, 2011;Lopes et al, 2011;Das and Dkhar, 2011;Grantina et al, 2011;Schmid et al, 2011;Wang et al, 2012;Stockdale et al, 2013;Hartmann et al, 2014;Lupatini et al, 2017). These workers have also reported higher population of microorganisms in organic farm in comparison to conventional farms.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 98%
“…Long-term soil fertilization strategies play a significant role in the alteration of soil biological properties, and thus may affect soil functioning and quality (BĂźnemann et al, 2018). Several studies showed that soil microbial communities are influenced by long-term fertilization strategies (Hartmann et al, 2015;Francioli et al, 2016;Lupatini et al, 2017). The use of mineral fertilizers in conventional agriculture has contributed to increased crop productivity over the last decades (Robertson and Vitousek, 2009).…”
Section: Introductionmentioning
confidence: 99%